Flow speed measurements using GPS over Blåskimen Island in Western Dronning Maud Land - Matsuoka, Kenichi (Norwegian Polar Institute, 2016)
This dataset provides static GPS measurements in a strain grid setup over Blåskimen Island, Fimbul Ice Shelf, western Dronning Maud land. The data were collected during the expeditions to the DML in years 2013 and 2014. The measurements were taken with respect to a local fixed base stations at the summit. The coordinates of the base stations were fixed using Canadian Precise Point Positioning. Rest of the data were processed differentially using GAMIT, GLOBK7TRACK software package. The data were projected to a polar stereographic projection parallel to 71°S (EPSG 3031). It is used to obtain the flow speed changes over the ice rise. It is provided in MATLAB (.mat) file format named ‘IRD_flow_speed.mat’ containing: LAT1 and LON1 shows the coordinates as per WGS84 ellipsoid in decimal degrees for the 2013 survey points whereas, LAT2 and LON2 shows the coordinates for the year 2014. Similarly X1,Y1 and X2,Y2 show the coordinates in polar stereographic for the years 2013 and 2014. U and V are the horizontal and vertical component of flow speed in ma-1 w.r.t. 2013 survey points. See the following manuscript for further details: Goel, V., Brown, J., and Matsuoka, K.: Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica, The Cryosphere Discuss., https://doi.org/10.5194/tc-2017-61, in review, 2017.